Synergistic p-doping of polymer-wrapped small-diameter single-walled carbon nanotubes by tris(pentafluorophenyl)borane - Lindenthal, Sebastian; Rippel, Daniel; Kistner, Lucas; Hawkey, Angus; Zaumseil, Jana (The journal of physical chemistry. C, Energy, materials, and catalysis, 2025)
Despite its comparatively low electron affinity, tris(pentafluorophenyl)borane (BCF) has been widely explored as an efficient molecular p-dopant for semiconducting polymers through the formation of Brønsted acidic complexes as well as its high affinity toward Lewis-basic nitrogen moieties. Many conjugated polymers that are used for selective wrapping and dispersion of semiconducting single-walled carbon nanotubes (SWCNTs) such as poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(6,6′-(2,2′-bipyridine))] (PFO-BPy) contain nitrogen moieties that should promote interaction with BCF. Here, we demonstrate that BCF indeed efficiently p-dopes even small-diameter (6,5) SWCNTs that are wrapped with large-bandgap PFO-BPy as corroborated by bleaching of the main absorption peaks and the appearance of red-shifted trion absorption and emission. In contrast, SWCNTs that are wrapped with poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PFO) without any Lewis-basic nitrogen moieties are only mildly doped. UV-Vis-NIR absorption, 19F NMR, and 11B NMR spectra confirm that BCF dopes the bipyridine-containing PFO-BPy but not PFO, thus leading to a proposed doping mechanism that relies on the unique interactions between BCF, the bipyridine moieties in PFO-BPy, and the nanotubes. Since BCF doping of PFO-BPy-wrapped (6,5) SWCNTs is more efficient than doping with F4TCNQ and more stable than doping with AuCl3, it provides a reliable alternative for spectroscopic studies of the interactions of charge carriers and excitons in SWCNTs.
Online verfügbar: 05.März 2025
Gesehen am 12.08.2025